Queer and COVID‑19 Positive: Contagion, Suspicion, and Stigma - Zwalf, Holly; Sperring, Samantha (Anthropologica, 2021)
I was one of the earliest cases of COVID‑19 in Australia. When I infected my partner, a trans man with cystic fibrosis, he was nine months pregnant. He birthed the baby during our nine days of forced isolation in hospital, making medical history as the first COVID-positive person to give birth outside of China, and the first documented non-caesarean birth in the world. Unfortunately, this was not the happy event it should have been. Our experiences while in the hospital were deeply traumatic, and since recovery we have been subjected to ongoing stigma. The post-COVID body is “othered” by medical professionals and the general public, treated with an acute suspicion reminiscent of ableism or fatphobia towards non-normative bodies. These experiences of exclusion and alienation echo the stigma directed towards the HIV-positive community during the height of the AIDS epidemic and the historical bio-medical regulation of queer bodies as second-class citizens. Drawing on theories of queer temporality, we consider the liminality of living in a “post-COVID” body—on the threshold of wellness and social contagion—as a queer time-warping experience. We call into question normative narrations of healthy/diseased bodies by considering the post-COVID body’s treatment as continually contagious.